If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5x + -6 = 0 Reorder the terms: -6 + 1.5x = 0 Solving -6 + 1.5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1.5x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1.5x = 0 + 6 1.5x = 0 + 6 Combine like terms: 0 + 6 = 6 1.5x = 6 Divide each side by '1.5'. x = 4 Simplifying x = 4
| x(9x+22)+13=0 | | X^2-3x=12-3x-6 | | x/3+8=-4 | | -2a+4+3a=6-24 | | 12v^2+12v+6=0 | | x^2+16x-140=0 | | .2x=8000 | | 12v^2+12v+3=-3 | | (y*y-9)/(y*y+3y-18) | | 2x^2y+6x^2y^2-xy^2= | | 9*7-2x*81*2x-1=1 | | y*y-9/y*y+3y-18 | | 0=x^2+16x+37 | | 4=5x-6 | | (-7x^5y^5)(3xy^4)= | | y-7+1/4(y+2) | | (1/3)x+(1/6)=(-2/3)+(2/3) | | 3(x-1)=2(x+1)+2 | | 8m^2+10m^3= | | 8m^2-10m^3= | | 5z-4-3+2z=0 | | v=3/2r-1 | | -6m^3n^-7/3m^-4n^-4 | | a/3+4=-2 | | 3x+y=656 | | X+y=656 | | 12x+9=81 | | 2(x+6)=x+1 | | 3q-6=-4 | | 2(-x-8)=32-5+1 | | n+(-7)=-77 | | (-7/16)=x-(11/12) |